Morning glories (2010), volume 2 ebook - Spencer, Nick (Morning Glories (2010), 2015)
Collecting the second story arc of the smash series in one volume. Learn (some) of the secrets in the Glories' lives as we delve into their pasts and see how it affects their present. Each chapter focuses on a different Glory while maintaining the narrative and moving the mystery forward.. Author: Nick Spencer. Illustrator: Joe Eisma, Rodin Esquejo . 2011 Nick Spencer & Joe Eisma.